A Comparative study of intrathecal dexmedetomidine and fentanyl as adjuvants to Bupivacaine - Rajni Gupta; Reetu Verma; Jaishri Bogra; Monica Kohli; Rajesh Raman; Jitendra Kumar Kushwaha (Wolters Kluwer Medknow Publications, 2011)
Background: Various adjuvants have been used with local anesthetics in spinal anesthesia to avoid intraoperative visceral and somatic pain and to provide prolonged postoperative analgesia. Dexmedetomidine, the new highly selective α2-agonist drug, is now being used as a neuraxial adjuvant. The aim of this study was to evaluate the onset and duration of sensory and motor block, hemodynamic effect, postoperative analgesia, and adverse effects of dexmedetomidine or fentanyl given intrathecally with hyperbaric 0.5% bupivacaine. Materials and Methods: Sixty patients classified in American Society of Anesthesiologists classes I and II scheduled for lower abdominal surgeries were studied. Patients were randomly allocated to receive either 12.5 mg hyperbaric bupivacaine plus 5 μg dexmedetomidine (group D, n=30) or 12.5 mg hyperbaric bupivacaine plus 25 μg fentanyl (group F, n=30) intrathecal. Results: Patients in dexmedetomidine group (D) had a significantly longer sensory and motor block time than patients in fentanyl group (F). The mean time of sensory regression to S1 was 476±23 min in group D and 187±12 min in group F (P<0.001). The regression time of motor block to reach modified Bromage 0 was 421±21 min in group D and 149±18 min in group F (P<0.001). Conclusions: Intrathecal dexmedetomidine is associated with prolonged motor and sensory block, hemodynamic stability, and reduced demand for rescue analgesics in 24 h as compared to fentanyl.